Mobile Manipulator for Hospital Care Using Firebase - Varela-Aldás, José (2022)
The COVID-19 pandemic has shown that the use of the technology in medicine is no longer a luxury, but a necessity. The use of the robotics in the treatment of diseases and physical therapies is limited in Latin America due to the high acquisition and maintenance costs. This document proposes the design, development, and evaluation of a robotic system for the guided monitoring of patients, through remote control using a mobile application. Within the methodology, four phases were proposed: planning, design, development, and evaluation. The 3D design is done using the Tinkercad software, which facilitates the construction of the pieces using 3D printing technology. The ESP32 board is the main element that receives the signals from the sensors and controls the actions of the actuators through the orders received from Firebase. For the development of the application, App inventor is used, building a friendly and easy-to-use interface. To validate this proposal, experimental tests were carried out with two patients in a medical center. In addition, a parameter compliance questionnaire was applied to the robot, obtaining a score of 92.6%, and the mobile application obtained 72.5% in the usability test. All this confirms an efficient care proposal, with a reduced investment.